1989
DOI: 10.1152/jappl.1989.66.3.1219
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of maximal O2 uptake from O2 delivery in canine gastrocnemius in situ

Abstract: To test the hypothesis that maximal O2 uptake (VO2max) can be limited by O2 diffusion in the peripheral tissue, we kept O2 delivery [blood flow X arterial O2 content (CaO2)] to maximally contracting muscle equal between 1) low flow-high CaO2 and 2) high flow-low CaO2 conditions. The hypothesis predicts, because of differences in the capillary PO2 profile, that the former condition will result in both a higher VO2max and muscle effluent venous PO2 (PVO2). We studied the relations among VO2max, PVO2, and O2 deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 0 publications
5
45
0
Order By: Relevance
“…5 B, Table I). This single level of diffusional conductance at WRMAX is consistent with other studies (8,30,31) and the theory that diffusion limitation may play a role in determining V02mx,, in exercising muscle (4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5 B, Table I). This single level of diffusional conductance at WRMAX is consistent with other studies (8,30,31) and the theory that diffusion limitation may play a role in determining V02mx,, in exercising muscle (4).…”
Section: Discussionsupporting
confidence: 91%
“…Based on direct measurements of intracellular Po2 (28) and mathematical modeling (29) in maximally exercising muscle, previous analyses of diffusivity, not knowing PMITOO2, have limited their calculations to Vo2n,, where it was assumed cellular Po2 was very low ( 1-3 mmHg range) and so could be neglected (4,6,30,31). The present study has demonstrated that the assumption of a low intracellular P02 at V02m,., relied upon in these initial investigations, was valid and in fact is the case even at submaximal exercise intensities eliciting only 50% of VO2max (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These simulations explain quantitatively how O 2 diffusion may limit muscle oxidative metabolism at maximal contraction rate, as suggested from canine muscle data (25,29). However, at submaximal contraction, V O 2 on-kinetics are not affected by arterial O 2 content, implying the absence of O 2 diffusion limitation (24).…”
Section: Relationship Between Ipo 2 and Energy Demandsupporting
confidence: 60%
“…These effects can decrease RBC transit time thereby minimizing the temporal window for O 2EX (16). The importance of RBC transit time has been reported for both muscle and coronary circulation (24) In our study with Hb of about 3 g/dl at DO 2 CRIT , shortened transit times may be of particular importance because O 2 off-loading kinetics for Hb are two times slower than O 2 loading on Hb (24).…”
Section: Discussionmentioning
confidence: 60%